Contesting narratives: the Koh Tao tourists murders. Issue 3 (1st September 2016) - Cohen, Erik
Abstract : The gruesome murder of two British tourists in September 2014 on "paradisiac" Koh Tao, a world-renowned diving site in Thailand, attracted widespread international attention. The authorities therefore urged the police to swiftly resolve a case threatening foreign tourism arrivals and the country's image. Using Innes' concept of police "investigation narratives" in homicide cases, this report contrasts the narrative of the murders constructed by the police under pressure from the authorities, with a widespread counter-narrative, which criticized the police for scapegoating weak, illegal foreign labor migrants as the murderers, while allegedly covering for the real culprits. The article shows how a rigid adherence to the police's narrative, due to extraneous considerations, backfired on the police and the authorities and embroiled them in a widening national and international dispute, with high stakes for the prestige of the Prime Minister, the reputation of the police and the image of the country. Under the circumstances, the prosecution and eventually the lower instance court accepted the police's narrative, leading to a death sentence for the accused, which aroused wide indignation and protest, and is currently under appeal. In conclusion it is argued that Innes' concept of investigation narratives has a political dimension, since such narratives can be strategically deployed by the police and used by the authorities for their own political ends, with deleterious implications for the dispensation of justice.